Belajar Sambil Bermain Lewat Desain - Liem, Claudia Melani; Kusumowidagdo, Astrid; Indrawan, Stephanus Evert (Aksen : Journal of Design and Creative Industry, 2015)
In today’s world, particularly in Indonesia, there are increasing in the development and the necessity of interior design’s business. It is mainly affected by changes in societies’ lifestyles and the expansion of the property markets along with investors began to extend to outside Java. Numerous problems encountered by the societies associated with the function and quality of interior space environments.The author aims to fulfill societies’ requirements through interior design consultant; named MYC. MYC assists and provides solutions to clients, through the results of consultation and design in accordance with the clients’ specifications, especially in the area of Makassar and Manado. Client satisfaction is the main goal of MYC, thus, MYC improves the quality of life through design is a solution to the problems faced.EbenHaezar’s Kindergarten School in Manado is one of MYC’s design implementation. The kindergarten has a concept of Fun, Balancing and Intelligence, where this concept offers a balance between learning and play for children that are identical to playing and learning. Fun concept is supported by the use of shape and color in every room that aims to brighten the atmosphere of the school considering the building is dominantly occupy with children around two to six years old. In addition, warm and safe concepts are emphasized by applying material that is warm natural, such as on the floor using wood vinyl flooring as to create coziness to the children to feel like their own house.